Painting feminism: early works of Núria Pompeia (1967-1975) - Jareño, Claudia; Sanz Gavillon, Anne-Claire (Filanderas, 2018)
The purpose of this article is to dig in the first works of the Catalan cartoonist Núria Pompeia. The authors suggest that, even though it has almost not been studied yet by academic researchers, this work forms a key material to understand the gradual waking up of a collective feminine consciousness even before the end of the Francoist dictatorship. Examining this previous process/step is therefore necessary to apprehend the quick development of the feminist movement in post-dictatorship Spain. In addition, this article aims to show that even using an almost mude drawing, Núria Pompeia is able to elaborate step by step an early, complex and complex feminist discourse.